Ptpn11 Deletion in CD4+ Cells Does Not Affect T Cell Development and Functions but Causes Cartilage Tumors in a T Cell-Independent Manner - Miah, S. M. Shahjahan; Jayasuriya, Chathuraka T.; Salter, Alexander I.; Reilly, Emma C.; Fugere, Céline; Yang, Wentian; Chen, Qian; Brossay, Laurent (Frontiers in Immunology, 2017)
The ubiquitously expressed tyrosine phosphatase SHP-2 (encoded by Ptpn11) is required for constitutive cellular processes including proliferation, differentiation, and the regulation of immune responses. During development and maturation, subsets of T cells express a variety of inhibitory receptors known to associate with phosphatases, which in turn, dephosphorylate key players of activating receptor signaling pathways. We hypothesized that SHP-2 deletion would have major effects on T cell development by altering the thresholds for activation, as well as positive and negative selection. Surprisingly, using mice conditionally deficient for SHP-2 in the T cell lineage, we show that the development of these lymphocytes is globally intact. In addition, our data demonstrate that SHP-2 absence does not compromise T cell effector functions, suggesting that SHP-2 is dispensable in these cells. Unexpectedly, in aging mice, Ptpn11 gene deletion driven by CD4 Cre recombinase leads to cartilage tumors in wrist bones in a T cell independent manner. These tumors resemble miniature cartilaginous growth plates and contain CD4-lineage positive chondrocyte-like cells. Altogether these results indicate that SHP-2 is a cartilage tumor suppressor during aging.